The supine coronal midaxillary approach to anterior quadratus lumborum block: case report - Diwan,Sandeep (2020)
Abstract Background: There are various approaches to perform an ultrasound guided Quadratus Lumborum Block (QLB). The lateral, posterior, anterior or trans muscular and subcostal paramedian are the various approaches described for performing a QLB. Each of these blocks are aimed to achieve a maximum spread with high volume and low concentration of local anesthetics. Case report: In this novel approach a curvilinear ultrasound probe was used with the patient lying in supine position. The probe was placed longitudinally in the mid axillary line to visualize Quadratus Lumborum Muscle (QLM) in the coronal plane. The needle was then introduced from cranial to caudal direction and catheters were inserted in the Anterior Thoracolumbar Fascia (ATLF) up to a distance of 4-5 cm in 24 patients for an anterior approach to acetabulum fractures. The needle tip and the Local Anesthetic (LA) spread was visible in all patients. All patients except 4 had excellent perioperative pain relief considering stable hemodynamics and VAS 2-3/10 for the first 48 hours. All patients received 1 g intravenous paracetamol each 8 hours. VAS in postoperative period was 2-3/10, in 20/24 patients. In the postoperative period, 4 patients complained of persistent pain, requiring intravenous fentanyl boluses and multimodal analgesia. Mean VAS score was 2.87 from 0-12 hours, 3.14 from 12-24 hours and 3.35 from 24-48 hours. There were no block-related complications in any patient. Conclusion: The supine midaxillary coronal approach to anterior QLB is an effective and feasible approach to QLB which can be performed in supine position.